Fish consumption, fish oil supplements and risk of atherosclerosis in the Tromsø study - Stein Harald Johnsen; Bjarne K. Jacobsen; Sigrid K. Brækkan; John-Bjarne Hansen; Ellisiv B. Mathiesen (Nutrition Journal, 2018)
Abstract Background Whether long-chain n–3 PUFAs of marine origin have an anti-atherogenic effect in the general population has hardly been studied. In this population-based study, we hypothesized that fatty fish and fish oil intake protect against development of novel atherosclerotic plaques and is associated with reduced plaque size. Methods We obtained questionnaire-based information on fish consumption and carotid ultrasonography from 3900 persons aged 45–74 years. The questionnaires were validated by measuring serum concentrations of PUFAs and triglycerides in a subgroup. At follow-up seven years later, 2983 (76%) went through a second ultrasound scanning. Logistic regression and general linear models were used to analyze the outcome (plaque presence and plaque area) as a function of fish consumption, including analyses stratified on fish oil supplements. Results At baseline, lean fish intake < 1 time/week vs. 1–1.9 times/week was associated with risk of plaque (OR 1.34, 95% CI 1.03–1.76). Fatty fish intake and use of fish oil supplements were not statistically significantly associated with atherosclerosis at baseline. In persons without plaque at baseline, total fish consumption ≥3 times/week vs. 1–1.9 times/week was associated with risk of novel plaque (OR 1.32, 95% CI 1.01–1.73) and larger plaque area (1.76 mm2 vs. 1.46 mm2, p = 0.02) at follow-up. Adjustments for use of fish oil supplements had no impact on the associations, and no interactions were seen between total, fatty or lean fish consumption and fish oil intake. Conclusions We found no protective effect of fatty fish eating or fish oil supplements on atherosclerotic plaque formation or plaque area in a general population. Lean fish consumption was associated with a reduced risk for plaque in cross-sectional analysis, suggesting that the beneficial effects of fish consumption on atherosclerosis may be mediated through other mechanisms than n-3 PUFAs.